2019
DOI: 10.2147/opto.s217722
|View full text |Cite
|
Sign up to set email alerts
|

<p>Epidemiology and molecular diagnosis of acute conjunctivitis in patients attending Hamadan, west Iran ophthalmology clinics 2016–2017</p>

Abstract: BackgroundViruses are considered the most common cause of infectious conjunctivitis. PCR has been approved as the best standard method to diagnose viral conjunctivitis. This study was conducted to investigate epidemiological patterns of conjunctivitis in Hamadan, west Iran. In addition, the frequency of the most important cause of infectious conjunctivitis diagnosed by PCR and its seasonal variations and association with certain socioeconomic and health factors were studied.MethodsIn this cross-sectional study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Most of the etiologies of EPS are associated with a pathophysiological inflammatory mechanism [ 15 ]. Viral conjunctivitis is considered the most common etiology of infectious conjunctivitis [ 16 - 19 ]. In our study, we found a high prevalence of EPS that occurred post-viral conjunctivitis (86.4%).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the etiologies of EPS are associated with a pathophysiological inflammatory mechanism [ 15 ]. Viral conjunctivitis is considered the most common etiology of infectious conjunctivitis [ 16 - 19 ]. In our study, we found a high prevalence of EPS that occurred post-viral conjunctivitis (86.4%).…”
Section: Discussionmentioning
confidence: 99%
“…Conjunctivitis is one of the main causes of redness and discharge of the eyes, and its prevalence varies according to the patients’ gender and age, and different seasons of the year [ 16 ]. To the best of our knowledge, there is little evidence available in Iran about conjunctivitis caused by M. catarrhalis , although some studies have been performed on the bacterial and viral agents that cause the disease [ 17 , 18 ]. We observed a higher occurrence of conjunctivitis in male (65%) when compared to female (35%) patients.…”
Section: Discussionmentioning
confidence: 99%
“…[ 5 ] Furthermore, it has been reported that 94.5% of patients with suspected viral conjunctivitis or keratoconjunctivitis were positive for adenovirus. [ 6 ]…”
Section: Introductionmentioning
confidence: 99%